PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY) TEMA KEBAKARAN LAHAN DAN HUTAN (KARLAHUT) PADA MATA PELAJARAN BIOLOGI KELAS X SMA - Rolin, Mayolla Adha; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The issue of land and forest fires require an effort comprehensively, byinstilling the values of knowledge. The value of the integrated knowledge on subjects inthe school of biology in particular. The purpose of this study is to increaseunderstanding and knowledge learners regarding land and forest fires and peat swampecosystem so expect future learners can perform preventive measures against theproblem of land and forest fires. This research was carried out in the laboratory ofBiology Education Department PMIPA FKIP University of Riau and SMAN 1 Tambangin January – March 2016. This type of research is development research using modelADDIE conducted up to the stage of development. There are five Student Worksheets(LKPD) developed. Data collection instruments in the research is the assessmentsheetsof validation, and student response. After LKPD developed, validated by 4 peoplevalidator then conducted tests I on 19 students semester 2 Biology education, and URfree trial II on 19 person learners Class X in SMAN 1 Tambang. The results of thevalidation shows the average score aspects of eligibility of the contents of 5 LKPDdeveloped is 3.48 category is valid, the average score of design aspects is a validcategory, and 3.44 average score aspects of pedagogy is 3.67 valid categories. Theaverage score of the overall aspect of the five LKPD is 3.50 category is valid. Theresults of the first tests showed a mean score of 4.3 with category very well. The resultsof the second tests showed the mean score II 4.3 with category very well. The results ofstudents answer showed that mean score 78 with category valid. LKPD Based SETS thetheme of land and forest fires can provide understanding and knowledge about the landand forest fires and peat swamp ecosystem as well as indirectly can improve the attitudeof caring environment learners.Keywords: Development, LKPD, SETS, land and Forest Fires